Mothers as Home DJs: Recorded Music and Young Children’s Well-Being During the COVID-19 Pandemic - Cho, Eun; Ilari, Beatriz Senoi (Frontiers in Psychology, 2021)
As the COVID-19 pandemic continues to disrupt our lives in unimagined ways, families are reinventing daily rituals, and this is likely true for musical rituals. This study explored how parents with young children used recorded music in their everyday lives during the pandemic. Mothers (N = 19) of child(ren) aged 18 months to 5 years living in the USA played the role of home DJ over a period of one week by strategically crafting the sonic home environment, based on resources provided by the authors, in response to their children’s mood and state. Using a newly developed data collection tool, inspired by the Experience Sampling Method, a total of 197 episodes were collected about children’s engagement with recorded music. Findings showed that while mothers utilized music to fulfill various emotional needs, they tended to use it to maintain or reinforce their child’s positive mood rather than to improve a negative mood. Also, mothers’ reports suggested various ways that young children engaged with music, being aligned with the multimodal nature of their musical experiences. Lastly, mothers reported that their strategic approaches to use recorded music seemed to help their children feel less distressed and happier, and this, in turn, aided in the reduction of some of the burdens associated with parenting.